Absence of the mental foramen in dry human mandibles - de Freitas, Valdemar [UNESP]; Madeira, M. C. [UNESP]; Fillio, J. L. Toledo [UNESP]; Chagas, C. F. [UNESP] (Karger Publishers, 1979)
The absence of the mental foramen was investigated in 1,435 dry human mandibles (2.870 sides). The foramen was absent twice in the right side (0.06%) and once in the left side (0.03%). The meaning of this anatomical variation was commented. © 1979 S. Karger AG, Basel.
Keywords: Anatomical variation; Mandible; Mental foramen; Osteology